Temporal trend of mortality from malignant neoplasm of the larynx in Brazil: Epidemiological analysis based on DATASUS data (1980-2019) (Research, Society and Development, 2025)
Objective: To analyze the temporal trend of mortality from malignant neoplasm of the larynx in Brazil and regions, using data from the Mortality Information System (SIM/DATASUS). Methodology: Descriptive epidemiological time series study, using secondary data from SIM/DATASUS for the period 1980-2019. A total of 112,693 deaths from malignant neoplasm of the larynx (ICD-10: C32; ICD-9: 161) were analyzed, stratified by sex, age group, geographic region and year of occurrence. Crude and age-adjusted mortality rates, temporal trend analysis and Annual Percent Change (APC) were calculated. Results: Male predominance was observed (87.3%; ratio 7.7:1), with concentration in the 60-69 years age group (31.4%). The Southeast region accounted for 49.0% of deaths. The temporal trend showed growth until 1999, followed by significant decline from 2000 onwards (APC 2009-2019: -1.6%). Adjusted rates decreased 38.7% between 2000-2019. Conclusion: Mortality from laryngeal cancer in Brazil shows a significant decreasing trend, reflecting the impact of tobacco control policies. Continuous monitoring is essential for evaluating public policies and guiding prevention strategies.